Magnetic Properties of GaAs/NiFe Coaxial Core-Shell Structures - Monaico, Eduard; Morari, Vadim; Kutuzau, Maksim; Ursaki, Veaceslav V.; Nielsch, Kornelius; Tiginyanu, Ion M. (Materials, 2022)
Uniform nanogranular NiFe layers with Ni contents of 65%, 80%, and 100% have been electroplated in the potentiostatic deposition mode on both planar substrates and arrays of nanowires prepared by the anodization of GaAs substrates. The fabricated planar and coaxial core-shell ferromagnetic structures have been investigated by means of scanning electron microscopy (SEM) and vibrating sample magnetometry (VSM). To determine the perspectives for applications, a comparative analysis of magnetic properties, in terms of the saturation and remanence moment, the squareness ratio, and the coercivity, was performed for structures with different Ni contents.
CRIS-Team Scopus Importer:2023-03-20
Keywords: anodization; coercive force; core-shell structures; electroplating; hysteresis loop; magnetic properties; nanowires; remanence ratio